Back Cover: 2‐Amino[1, 2, 4]triazolo[1, 5‐c]quinazolines and Derived Novel Heterocycles: Syntheses and Structure–Activity Relationships of Potent Adenosine Receptor Antagonists (ChemMedChem 20/2016). (19th October 2016) - Burbiel, Joachim C.; Ghattas, Wadih; Küppers, Petra; Köse, Meryem; Lacher, Svenja; Herzner, Anna‐Maria; Kombu, Rajan Subramanian; Akkinepally, Raghuram Rao; Hockemeyer, Jörg; Müller, Christa E.
Abstract : The back cover picture shows the structures of novel adenosine receptor antagonists. They compete with the natural agonist adenosine for its binding site at one or more of the four adenosine receptor subtypes. Compounds with specificity for the A3 receptor subtype were obtained. In addition, multitarget drugs were developed including dual A1 /A3 antagonists. Pan‐antagonists blocking all four receptor subtypes were synthesized, which display a similar profile as the natural product caffeine, but are 1000‐fold more potent. More information can be found in the Full Paper by Christa E. Müller et al. onpage 2272 in Issue 20, 2016 (DOI:10.1002/cmdc.201600255 ).